An Assessment of Skills in the Formal Sector Labor Market in Bangladesh : A Technical Report on the Enterprise-Based Skills Survey 2012 - World Bank (Washington, DC, 2014)
Education and skill development have played a crucial role in economic growth, poverty reduction and social transformation in Bangladesh, particularly the inclusion of women in the labor force in the last decade. Bangladesh has made impressive gains in improving access to education, reaching the Millennium Development Goals (MDG) of gender parity at the primary and secondary levels. Increased access to secondary education among girls over the past twenty years appears to have produced a powerful agent of social mobility as it is likely that many of the young girls who benefitted from the female stipends in the early 90s have now entered the labor market and may be enjoying higher earnings than older female cohorts. The widespread entry of women into the labor market has been a leading factor in the rapid expansion of the garment industry. With around USD 15 billion in export value in 2010, the readymade garment industry is currently Bangladesh's most important industry sector (McKinsey and Company 2011). In this context, a policy note on the skills development is being prepared to discuss the issues of the linkage between education and skills development and the labor market. The policy note, together with two other policy notes on access and equity, and quality of education, will be part of the Bangladesh Education Sector Review (ESR). The ESR is developed for diagnosing the current educational situation in Bangladesh and discusses different policy options for the way forward. The skills development policy note aims to assess the flow and stock of today's skills demands and supply, in the areas of formal and informal sector labor market, as well as the overseas labor market where a large number of Bangladesh seeks for employment opportunities. It also aims to discuss the skills required for Bangladesh to develop when achieving the status of the middle income country as stipulated in the vision 2021. As part of the skills policy note, the Enterprise-based Skills Survey (ESS) has been conducted. This background report documents the technical properties of the ESS and discusses the general results of the survey.